2017
DOI: 10.1080/08820538.2017.1284870
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Parental Myopia on Children’s Myopia in Different Generations of Parent-Offspring Pairs in South Korea

Abstract: With myopia, the environmental portion of the phenotypic variance increased and the additive genetic portion decreased as South Korea became more urbanized. With high myopia, the additive genetic portion remained roughly constant at approximately 60%, despite the urbanization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In a study on the prevalence of ametropia in the second generation of Australian school age children, the prevalence of myopia among the second-generation Australian school age children in the Middle East was similar to that of children in other school districts in Australia and higher than that reported in the Middle East [29]. Some studies even showed that environmental factors played a greater role in these two factors [30, 31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on the prevalence of ametropia in the second generation of Australian school age children, the prevalence of myopia among the second-generation Australian school age children in the Middle East was similar to that of children in other school districts in Australia and higher than that reported in the Middle East [29]. Some studies even showed that environmental factors played a greater role in these two factors [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent clinical trial among 6-year-old children in Guangzhou, China, the incidence of myopia was significantly reduced over the 3 years after the addition of 40 min of outdoor activity to the daily curriculum [13]. When considering that environmental factors play a leading role in myopia [30, 31, 58], some preventive methods should be implemented, such as increasing the time of outdoor activities, making the indoor light closer to that of the outdoors, avoiding late sleep, and using atropine and other effective measures.…”
Section: Discussionmentioning
confidence: 99%
“…10 In another study on high myopia across three different generations in Korea, results showed that the environmental portion of the phenotypic variance increased and the additive genetic portion decreased as South Korea became more urbanised. 33 Therefore, it remains to be established how geneenvironment interactions contribute to myopia within various populations. 2 In the present study, we analysed the effects of perinatal factors, such as delivery manner, delivery mode and pregnancy diseases, on the prevalence of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…There are some further considerations around parental myopia as a risk factor. The additive genetic portion of phenotypic variance is smaller in younger families, reflecting the trend for increasing environmental influences 81. The odds of a child with two myopic parents becoming myopic is thus different to the odds of a myopic child having two myopic parents.…”
Section: Background To the Need For Myopia Controlmentioning
confidence: 96%